Beyond Consent in Research. (27th May 2014) - BELL, EMILY; RACINE, ERIC; CHIASSON, PAULA; DUFOURCQ-BRANA, MAYA; DUNN, LAURA B.; FINS, JOSEPH J.; FORD, PAUL J.; GLANNON, WALTER; LIPSMAN, NIR; MACDONALD, MARY ELLEN; MATHEWS, DEBRA J. H.; MCANDREWS, MARY PAT
<x content-type="archive" xml:space="preserve">Abstract</x> Neuroethics Now welcomes papers addressing the ethical application of neuroscience in research and patient care, as well as its impact on society.